2014
DOI: 10.1111/ene.12449
|View full text |Cite
|
Sign up to set email alerts
|

Retinal nerve fiber layer thickness and thalamus pathology in multiple sclerosis patients

Abstract: Lower RNFLT is associated with microscopic tissue injury in NA regions of the brain and with neurodegeneration of the deep gray matter and thalamus in RR-MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…More recently, Mühlau et al (Muhlau et al, 2013) found that WM lesions and PUL atrophy are spatially related in MS, with axonal transection within WM lesions and subsequent degeneration along the axonal projections being the most plausible explanation. Gabilondo et al (Gabilondo et al, 2014) showed retro- and anterograde trans-synaptic neuronal degeneration in the visual pathway and Zivadinov et al (Zivadinov et al, 2014) reported a trend toward associations between retinal nerve fiber layer thickness in RRMS patients and microstructural damage in the thalamus, in particular, volume changes in the GT and PUL.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Mühlau et al (Muhlau et al, 2013) found that WM lesions and PUL atrophy are spatially related in MS, with axonal transection within WM lesions and subsequent degeneration along the axonal projections being the most plausible explanation. Gabilondo et al (Gabilondo et al, 2014) showed retro- and anterograde trans-synaptic neuronal degeneration in the visual pathway and Zivadinov et al (Zivadinov et al, 2014) reported a trend toward associations between retinal nerve fiber layer thickness in RRMS patients and microstructural damage in the thalamus, in particular, volume changes in the GT and PUL.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the volume of the entire thalamus was associated with retinal damage in 2 previous studies: one of them used voxel-based morphometry (VBM) and showed that retinal axonal loss (measured as thinning of the retinal nerve fiber layer [RNFL]) was associated with a decrease in the volume of thalamus and the visual cortex. 2 The other study showed a cross-sectional correlation between RNFL and thalamic volume in MS. 30 However, the thalamus has multiple nuclei with many different functions and shows structural changes early in the course of MS. 31 Moreover, neuroaxonal loss in the retina correlates with brain atrophy 32 and is thought to generally reflect neurodegenerative processes in MS. 33 Thus, a specific assessment of the LGN is crucial to investigate neurodegeneration occurring specifically in the visual pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of retrograde transsynaptic neurodegeneration on retinal atrophy was shown in previous studies in established MS. 27,28 Our findings indicate that such a mechanism also occurs in the earliest stages of demyelination. This finding is also supported by two previous studies showing the association of pRNFL with nTBV 6,29 and nWMV 29 in early MS. Several cross-sectional studies in established MS showed that both mGCL/GCIPL 27,30,31 and pRNFL 27,3032 of non-ON eyes are associated with volumetric brain measurements. However, a longitudinal study showed that rate of atrophy in mGCIPL, but not pRNFL, was related to the rate of nTBV, nGMV, nTV loss, and also the lesion accumulation rate.…”
Section: Discussionmentioning
confidence: 99%